Technical report: modelling of Wau Bulan curves / Liyana Afifi Saiful Bahri, Nadiah Ahmad Awang Toshiya and Wan Madihah Wan Ismail - Saiful Bahri, Liyana Afifi; Ahmad Awang Toshiya, Nadiah; Wan Ismail, Wan Madihah (2017)
Ethnomathematics shows the relationship between mathematical idea and culture that must be embedded in order to us understand the diverse culture. One of the cultures in Malaysia is playing Wau Bulan (moon kite). By taking the concepts of making Wau Bulan, a new research is made that relate it with Mathematics. It is to find the Wau Bulan curves shape by using three different equations which are Quadratic equation, Bezier equation and Hermite equation. To do this research, the data of a model of Wau Bulan is collected from the craftsmen in Kelantan that mastered in making Wau Bulan. The data obtained is then converted to be coordinates on the Cartesian Plane and used to create the Wau Bulan shape by using Maple software using Quadratic equation, Quadratic Bezier equation and Cubic Hermite equation. The result obtained is compared to the actual shape of Wau Bulan to get the best fitted curves which is Cubic Hermite equation.